(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
An examination of the inmate population can provide vital insight into the relationships between socio-political and social control institutions and punishment. Thus, this essay analyses the changes in scale, composition, and management of inmates in Nigeria. To offer pertinent data for the study, secondary sources, such as official statistics, reports, and data from earlier academic studies, were employed. The study found that the inmate population in Nigeria continues to increase due to arbitrary arrests by the police, delays in sentencing, and theM inability to execute condemned criminals, among others. The majority of the inmates are poor, uneducated, and unsentenced, which highlights the structural inequality that exists and the unfair nature of the justice system. The management of the inmate population shows that prisons in Nigeria are still more punitive than corrective. Thus, there is a need for urgent intervention from the government and concerned institutions to rescue the prison system. Word count 144